Hypervirulent and hypermucoviscous extended-spectrum β-lactamase-producing Klebsiella pneumoniae and Klebsiella variicola in Chile. Issue 1 (31st December 2021) - Morales-León, F.; Opazo-Capurro, A.; Caro, C.; Lincopan, N.; Cardenas-Arias, A.; Esposito, F.; Illesca, V.; Rioseco, M. L.; Domínguez-Yévenes, M.; Lima, C. A.; Bello-Toledo, H.; González-Rocha, Gerardo
ABSTRACT: Convergence of virulence and antibiotic-resistance has been reported in Klebsiella pneumoniae, but not in Klebsiella variicola . We, hereby, report the detection and genomic characterization of hypervirulent and hypermucoviscous K. pneumoniae and K. variicola recovered in Chile from health-care associated infections, which displayed resistance to broad-spectrum cephalosporins. One hundred forty-six K. pneumoniae complex isolates were screened by hypermucoviscosity by the "string test." Two hypermucoid isolates, one hypermucoviscous K. pneumoniae (hmKp) and one K. variicola (hmKv), were further investigated by whole-genome sequencing. In vivo virulence was analyzed by the Galleria mellonella killing assay. In silico analysis of hmKp UCO-494 and hmKv UCO-495 revealed the presence of multiple antibiotic-resistance genes, such as bla CTX-M-1, bla DHA-1 and bla LEN-25 among others clinically relevant resistance determinants, including mutations in a two-component regulatory system related to colistin resistance. These genetic features confer a multidrug-resistant (MDR) phenotype in both strains. Moreover, virulome in silico analysis confirmed the presence of the aerobactin gene iutA, in addition to yersiniabactin and/or colicin V encoding genes, which are normally associated to high virulence in humans. Furthermore, both isolates were able to kill G. mellonella and displayed higher virulence in comparison with the control strain. In summary, the convergence of virulence and the MDR-phenotype in K. pneumoniae complex members is reported for the first time in Chile, denoting a clinical problem that deserves special attention and continuous surveillance in South America.